Mortality in Sub-Saharan Africa: What is Killing Adults Aged 15-59 Years in Zambia? - Vesper H. Chisumpa; Clifford O. Odimegwu; Nandita Saikia (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2019)
The question of cause-of-death remains of interest among demographers, epidemiologists and public health researchers. Adults in the age group 15-59 years play a significant role in the socio-economic development of a country. However, in most of sub-Saharan African countries, the coverage and accuracy of data on adult mortality has been deficient compared to that of under-five (age group 0-4) mortality. As a result, little research exists on causes-of-death in this age group in most of sub-Saharan Africa and adult mortality remains a health burden for many countries in this part of Africa. Using the 2010-2012 Zambia Sample Vital Registration with Verbal Autopsy (SAVVY) survey data and computing age-sex and cause-specific death rates and ratios as well as constructing cause-deleted life tables, this study examined the causes-of-death among adults in age group 15-59 years. The study found that HIV/AIDS was the major leading cause-of-death across all demographic and socioeconomic background characteristics of the deceased adults. HIV/AIDS deaths increased by age and peaked in age group 35-39 and were higher among females than males. Injuries and accidents were the second leading cause-of-death among males while among females it was tuberculosis. Injuries and accidents were more prevalent in age group 15-35, the highly educated and the never married. Diseases of the circulatory system were the third leading cause-of-death among female decedents while tuberculosis was the third leading cause of death among males. Malaria was the fourth leading cause-of-death for both males and females. Adult deaths attributable to non-communicable diseases were more evident in older ages 45-59. Eliminating HIV/AIDS as a cause of death would have the most impact in reducing adult mortality in Zambia and contribute significantly to the number of additional years of life gained compared to eliminating the other causes-of-death. Therefore, health programmes and interventions on HIV/AIDS should be further supported and strengthened as they would significantly contribute to the reduction of adult mortality in Zambia in line with sustainable development goals (SDGs).
Keywords: 300; Cause of death; adult mortality; verbal autopsy; cause-specific mortality; HIV/AIDS; Zambia